Bio-Packaging Material Impact on Blueberries Quality Attributes under Transport and Marketing Conditions - Bof, María Julieta (2021)
Blueberries are highly appreciated for their high antioxidant content but are also particularly susceptible to fungal deterioration. In this work, corn starch and chitosan, byproducts of the fishing industry, as well as active compounds obtained from citrus processing waste were used to obtain active biodegradable film packaging. Blueberries were packed in corn starch–chitosan (CS:CH) films and in active films containing lemon essential oil (LEO) or grapefruit seed extract (GSE). The effects of film packaging on the quality parameters of berries and the fungal incidence of disease during storage were studied and compared to benchmark materials. A conservation assay simulating transport and commercialization conditions was conducted. Blueberries packed in CS:CH films showed antioxidant capacity values closer to those packed in commercial PET containers (Clamshells), preserving 84.8% of the initial antioxidants content. Fruit packed in LEO films exhibited the greatest weight loss and rot incidence, and poor surface color. CS:CH and GSE films controlled the fruit respiration rate and weight loss, therefore they are materials with adequate barrier properties for blueberries conservation. Bags formulated with GSE showed adequate barrier properties to maintain fruit quality attributes without the incidence of rottenness, being an interesting option for blueberries exportation.